2019
DOI: 10.3892/etm.2019.8330
|View full text |Cite
|
Sign up to set email alerts
|

miR‑155 promotes fibroblast‑like synoviocyte proliferation and inflammatory cytokine secretion in rheumatoid arthritis by targeting FOXO3a

Abstract: The present study aimed to explore the expression and effects of microRNA (miR)-155 in synovial fibroblasts of patients with rheumatoid arthritis (RA). A total of 89 synovial tissues from RA patients and 49 control synovial tissues were collected, and the levels of miR-155 were measured by reverse transcription quantitative-PCR and western blotting. Fibroblast-like synoviocytes (FLS) were isolated from synovial tissues from the control group and were used to evaluate the roles of miR-155 and forkhead box prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Thus, for example, early studies perhaps surprisingly reported that miR-155 plays a joint-protective role in RA SFs, having been associated with downregulation of MMP1 and MMP3, mediators that promote SF proliferation and invasion, as well as bone destruction 35, 36, 38, 39, 46 . However, although these studies also indicated that miR-155 did not impact on MMP9 or MMP13 expression or modulate spontaneous or stimulated (TLR ligands/cytokines) TGF β or IL-6 production 41, 47 , more recent work has identified a key role for this miR in driving (spontaneous and TNF α -stimulated) pathogenic responses (proliferation as well as IL-1 β and IL-6 production) via downregulation of its target FOXO3 4850 , which acts to suppress these functional outcomes in RA-SFs 51 . Thus, given the interactions of miR-155 with multiple TLR and cytokine (IL-1 β , IL-10, IL-17, TNF α , GM-CSF) pathways implicated in regulating arthritogenesis 38, 39 , we further investigated the role of this element in SF pathogenesis and ES-62-mediated protection.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, for example, early studies perhaps surprisingly reported that miR-155 plays a joint-protective role in RA SFs, having been associated with downregulation of MMP1 and MMP3, mediators that promote SF proliferation and invasion, as well as bone destruction 35, 36, 38, 39, 46 . However, although these studies also indicated that miR-155 did not impact on MMP9 or MMP13 expression or modulate spontaneous or stimulated (TLR ligands/cytokines) TGF β or IL-6 production 41, 47 , more recent work has identified a key role for this miR in driving (spontaneous and TNF α -stimulated) pathogenic responses (proliferation as well as IL-1 β and IL-6 production) via downregulation of its target FOXO3 4850 , which acts to suppress these functional outcomes in RA-SFs 51 . Thus, given the interactions of miR-155 with multiple TLR and cytokine (IL-1 β , IL-10, IL-17, TNF α , GM-CSF) pathways implicated in regulating arthritogenesis 38, 39 , we further investigated the role of this element in SF pathogenesis and ES-62-mediated protection.…”
Section: Resultsmentioning
confidence: 99%
“…no. ST316; Beyotime Institute of Biotechnology,) was added into each well and cultured at 37˚C and 5% CO 2 for 4 h. Then, 150 µl dimethyl sulfoxide (dMSO) was utilized to dissolve the formazan after discarding the liquid in each well as previously described (29,30). determination of the absorbance at 490 nm was performed using a microplate reader (BioTek Instruments, Inc.).…”
Section: Induction Of Arthritis and The Culture And Identification Ofmentioning
confidence: 99%
“…It has been supposed that the increase in TNF-α and IL-1β expressions might be due to the decreased expression of SOCS1 (suppressor of cytokine signaling protein 1) by miR-155 [45]. Other studies demonstrated that miR-155 targets FOXO3a (forkhead box protein O3a) leading to the increased expression of TNF-α, IL-1β and IL-6 [48]. Moreover, other studies confirmed that miR-155 targeted FOXO3a as well as STAT1 [40], APAF-1 (apoptotic peptidase activating factor 1) and caspase 10 [47].…”
Section: Effects Of Mirs On Pro-inflammatory Cytokines Expression In Human Cell Culture: Meta-analysismentioning
confidence: 99%